STATUS KEBERSIHAN MULUT DAN KESEHATAN PERIODONTAL PASIEN YANG DATANG KE KLINIK PERIODONSIA RSGM UNIVERSITAS JEMBER PERIODE AGUSTUS 2009 – AGUSTUS 2010 - Depi Praharani; Tantin Ermawati; Peni Pujiastuti (Fakultas Kedokteran Gigi Universitas Jember, 2011)
Level of oral hygiene have a close relationship with periodontal health status; where good oral hygiene will minimize the occurrence of periodontal disease. Aims of this study were to assess the oral hygiene status and periodontal health patients that come to Department of Periodontics of Jember University Dental Hospital at August 2009 until August 2010. This type of research is an observational study of clinical (cross sectional). A total of 155 sample (87 males and 66 females) were examined by using Oral Hygiene Index-Simplified (OHI-S) and Periodontal Index. Good oral hygiene was seen in 11% of total sample examined, 54,2% had fair oral hygiene and rest 34,8% showed poor oral hygiene. 0,6% of total sample examined had healthy periodontal, 18,1% had simple gingivitis, 41,3% had initial of periodontal disease destructive, 37,45 had periodontal disease destructive and 2,6% had terminal disease. Oral hygiene status and periodontal health examination revealed that majority of sample had fair oral hygiene and periodontal disease destructive.